Environment and Sustainable Development in Bangladesh: A Legal Study in the Context of International Trends - Mohammad, Nour (Mediterranean Journal of Social Sciences, 2012)
This paper attempts to focus on environment and sustainable development in Bangladesh. The researchwill be based upon theoretical sources and empirical data. An environment is a set of natural, artificial orman-made, physical, chemical and biological elements that make the existence, transformation anddevelopment of living organisms possible The appearance of the environmental law arose from the need toconserve the environment in order to avoid its destruction and, as a result, the danger that an adequatequality of life might disappear. By conservation we understand all those measures that are necessary topreserve the environment and natural resources. In modern times human development corresponds to theconcept of sustainable development and environment. It is a transverse theme derived from jointconsideration of the issue of the environment and environmental protection, and of all that concernsproduction in the development of a country or nation. It is a noble journey to make the constitution aweapon in as much as the environment should be fit for human development so that productive activitiesmay meet present needs without compromising those of future generations. The environment is anindependent value and needs as strict protection as other commonly agreed values such as the right toproperty or the right to life and health. The principal objectives are to study:- To explain come to anunderstanding of origin and growth as to the concept of environment and sustainable development indomestic and international laws and to show the rationality of enlisting the right to the environment as abasic right in the constitution that would help to protect this value from the detrimental activities of privateentities and also states and also to show the rationality of institutional development